Efficacy of zolpidem for dystonia: a study among different subtypes - Miyazaki, Yoshimichi; Sako, Wataru; Asanuma, Kotaro; Miki, Tetsuro; Kaji, Ryuji (Frontiers in Neurology, 2012)
Although there are some newly-developed options to treat dystonia, its medical treatment is not always satisfactory. Zolpidem, an imidazopyridine agonist with a high affinity on benzodiazepine subtype receptor BZ1(ω1) , was found to improve clinical symptoms of dystonia in a limited number of case reports. To investigate what subtype of dystonia is responsive to the therapy, we conducted an open label study to assess the efficacy of zolpidem (5-20mg) in 34 patients suffering from miscellaneous types of dystonia using the Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS). Patients were entered into the study if they had been refractory to other medications as evaluated by BFMDRS (no change in the previous 2 successive visits). After zolpidem therapy, the scores in the patients as a whole were decreased from 7.2±7.9 to 5.5±5.0 (P=0.042). Patients with generalized dystonia, Meige syndrome/blepharospasm, and hand dystonia improved in the scale by 27.8%, 17.8% and 31.0%, respectively, whereas no improvement was found in cervical dystonia patients. Overall response rate among patients were comparable to that of trihexyphenidyl. Zolpidem may be a therapeutic option for generalized dystonia, Meige syndrome and hand dystonia including musician’s. Drowsiness was the dose-limiting factor.